COST-EFFECTIVENESS ANALYSIS OF REMDESIVIR AND FAVIPIRAVIR THERAPY FOR THE TREATMENT OF COVID-19 IN ADULT PATIENTS AT THE HAJJ REGIONAL GENERAL HOSPITAL, EAST JAVA PROVINCE - Aditya Nugraha Halimbar; Amelia Lorensia; Dewi Ramadani (Jurnal Scientia, 2023)
Cases of Coronavirus Disease 2019 or COVID-19 from year to year show a tendency to increase spread worldwide, including Indonesia. COVID-19 is an infectious disease caused by a virus so redeliver and Favipiravir antiviral therapy is needed. This study compared the cost-effectiveness analysis of the drugs Ravipiravir and Remdesivir in COVID-19 disease at Haji Hospital Surabaya. This study compares observationally between 2 (two) alternatives using a hospital perspective and data collection carried out retrospectively in the period April 2021 to October 2021. The Cost Effectiveness Analysis method used is the Cost-Effectiveness Ratio (ACER). The results of the data obtained from the ACER cost-effectiveness analysis method in the Favipiravir group are Rp. 2,820,601.63 per day for length of stay and Rp. 6,485,071.79 per day for COVID-19-free time. While in the Remdesivir group Rp. 3,311,510.74 per day for the length of stay and Rp. 8,329,527.98 per day for COVID-19-free time. Meanwhile, the ICER analysis method is Rp. 6,195,280.50 per day for the length of hospitalization and Rp. 34,802,899 per day for COVID-19-free time. This study concludes that Favipiravir is more cost-effective than Remdesivir.